A study on Infant and Young Child Feeding (IYCF) practices among mothers attending a Tertiary Health Care Institution, Kolkata - Sukes Das; Nivedita Das; Malay Mundle; Palash Das (Al Ameen Medical College, 2018)
Background: Optimal feeding of infants and young children is of utmost importance for their better health and survival; deviation from this will result in infections, malnutrition or other morbidities and death as its worst consequence. Objectives: This study was undertaken to assess the IYCF practices among mothers having children of 0-23 Months, especially in accordance with WHO Indicators for the same. Methods: A Cross-Sectional Study was done among 360 mothers having children of 0-23 Months attending a tertiary health care institution, Kolkata during Oct-Nov, 2016. Results: Out of 170 infants aged 0-5 month 89.4% were exclusively breast fed; rest were predominantly breastfed. Around 30% babies were bottle-fed while only 33.3% children started complementary feeding from 6-8 months of age. Majority of the children i.e.70.0% of 6-23 months fulfilled minimum meal frequency whereas only 30% fulfilled minimum dietary diversity. Adequate diet was taken by 36.8 % of the 6-23 months old children. Conclusion: IYCF practices among mothers are still sub-optimal which need to be addressed urgently for attaining healthy childhood while avoiding morbidities and premature death.